Evaluasi Olahraga Gateball Kota Padang - Hilmainur Syampurma; Febri Yusuf; Willadi Rasyid; Asep Sujana Wahyuri (Pusat Studi Ilmu Keolahragaan, Fakultas Ilmu Keolahragaan, Universitas Negeri Padang, 2022)
The problem in this study is that the development of the city of Padang gateball has not been known. The purpose of this research is to find out the coaching of gateball sports in the city of Padang. This type of research is descriptive, this study was conducted on august 28, 2021 in the field of the Public Works and Public Housing Office (PUPR) of Padang city. The population in this study was the official and gateball athletes of the padang city which was 33 people. Sampling techniques using saturated sample techniques, then the samples in this study are: (10) the manager of the Padang City Pergatsi Pengkab who is still active, (2) the coach who handles gateball athletes, (21) gateball athletes. The data collection techniques in this study used research questionnaires and interviews, observations and documentation. The results of research 1) In the management of the board, the Pergatsi of Padang city runs with makeshift, including minimal facilities, less human resources. (2) coaches who handle gateball athletes, (21) gateball athletes. The data collection techniques in this study used research questionnaires and interviews, observations and documentation. The results of research 1) In the management of the board, the Pergatsi of Padang city runs with makeshift, including minimal facilities, less human resources. 2) The training program by the coach that is run is not in accordance with the existing training program. Namely the absence of physical exercise programs, mental exercise programs, tactical training programs and skill training programs by coaches. 3) The facilities and infrastructure owned by the City of Padang are sufficient.